Curricular needs for training telemedicine physicians: A scoping review. (1st November 2020) - Stovel, Rebecca G.; Gabarin, Nadia; Cavalcanti, Rodrigo B.; Abrams, Howard
Abstract: Purpose: The use of telemedicine, a part of 'Virtual Care', is rapidly entering mainstream clinical practice. The ideal curriculum for educating physicians to practice in this emerging field has not been established. We examined the literature to evaluate published curricula for quality and comprehensiveness through the lens of Competency-Based Medical Education (CBME). Methods: We performed a scoping review using CanMEDS as a framework. Peer-reviewed articles describing telemedicine training curricula were identified. Trainee population, curricular points, stage of implementation, evaluation depth, country, and citations (a marker of quality) were examined. Results: Forty-three curricula from 11 countries were identified, addressing all training levels and covering multiple specialties. Instructional methods included lectures (60.5%), hands-on experiences (76%), directed reading (24%), online modules (21%), reflection (13%), simulation (34%), and group discussions (16%). Hands-on curricula covered all CanMEDS roles more often. Twenty-nine of the implemented curricula were evaluated; 83% were rated positively. Conclusions: Our scoping review helps inform more comprehensive and efficacious curricula for teaching telemedicine. We suggest centering curricula on a competency-based, outcomes-oriented framework such as CanMEDS with multiple teaching modalities complementing hands-on experiences. This will facilitate rigorous telemedicine training to deliver on the promise of high-quality patient care.